A crise política e o impeachment: uma análise dos casos Collor e Dilma - Spada, Arthur Gonçalves (2023)
This paper sets out to make a comparative analysis of the impeachment processes opened in Brazil since 1988, which led to the removal of Fernando Collor de Melo in 1992, and Dilma Vana Rousseff in 2016, seeking to understand the particularities of the political crisis situations in which they were inserted and which led to the option of presidential removal being adopted. To do so, it starts by studying some approaches to analyzing the phenomenon of political crisis, which are relevant to understanding critical junctures and which can provide answers in the analysis of the processes studied. Secondly, it discusses the literature and comparative studies on impeachment, as well as the Brazilian presidential system, studying the evolution of the model established in 1988 and its contradictions. Finally, the paper turns to an analysis of the two cases studied, in order to reconstruct the critical processes, as well as taking a detailed look at the charges that were brought against both presidents, in an effort to understand the use of the impeachment instrument and applying the theory discussed above